Imagination of brand image for tourism industry - Mahadzirah, Mohamad; Wasib B., Latif; Md. Aminul, Islam (LLC CPC Business Perspectives, 2016)
The imagination of brand image for tourism industry is a combination of antecedents and moderators that create differential effects on customer response to the tourism marketing of the brand. As imagination consider framework of brand image for tourism industry. By constructing a conceptual framework of brand image for tourism industry will build a competitive advantage in the tourism marketplace. Indeed, recent trends in modern tourism marketing have changed tremendously, and study of a conceptual framework is increasingly becoming considerable to keep pace with this change. In this conceptual paper, authors have summarized the literature on currently prevailing concepts and approaches on brand image for tourism industry.